Responsibility of Oil and Gas (O&G) Companies to Protect Human Rights: The Case of Shell - Ishak, Ma Kalthum; Nordin, Rohaida (International Journal of Asian Social Science, 2019)
The role that companies play in domestic and international economies is fundamental and over the last few decades the impact of business on human rights has become increasingly visible. Their impact on human rights is an important discourse as they have the potential to make a direct and enduring impact on people’s lives. This research uses a case study methodology on an O&G company, Shell to examine its responsibilities and roles in respecting human rights from the theoretical and practical aspect. Assessment of Shell’s responsibilities is based on the operation of the company and its impacts on the following three aspects: environment; indigenous peoples; and labor. It is important to focus on these three aspects because they impacted most by the operations of the O&G companies. This study is divided into two parts; i) Shell’s responsibilities to protect human rights from the theoretical perspective in which the published data such as annual report and business guidelines are examine critically; ii) whether Shell has discharged its duties according to what they have declared in their business guidelines. This part examines cases of infringement of human rights involving Shell. This article concludes with recommendations on how O&G companies can respect human rights despite of their hazardous activities to environment, indigenous peoples and labor.